A Conserved Structural Role for the Walker-A Lysine in P-Loop Containing Kinases - Hajredini, Fatlum; Ghose, Ranajeet (Frontiers in Molecular Biosciences, 2021)
Bacterial tyrosine kinases (BY-kinases) and shikimate kinases (SKs) comprise two structurally divergent P-loop containing enzyme families that share similar catalytic site geometries, most notably with respect to their Walker-A, Walker-B, and DxD motifs. We had previously demonstrated that in BY-kinases, a specific interaction between the Walker-A and Walker-B motifs, driven by the conserved “catalytic” lysine housed on the former, leads to a conformation that is unable to efficiently coordinate Mg2+•ATP and is therefore incapable of chemistry. Here, using enhanced sampling molecular dynamics simulations, we demonstrate that structurally similar interactions between the Walker-A and Walker-B motifs, also mediated by the catalytic lysine, stabilize a state in SKs that deviates significantly from one that is necessary for the optimal coordination of Mg2+•ATP. This structural role of the Walker-A lysine is a general feature in SKs and is found to be present in members that encode a Walker-B sequence characteristic of the family (Coxiella burnetii SK), and in those that do not (Mycobacterium tuberculosis SK). Thus, the structural role of the Walker-A lysine in stabilizing an inactive state, distinct from its catalytic function, is conserved between two distantly related P-loop containing kinase families, the SKs and the BY-kinases. The universal conservation of this element, and of the key characteristics of its associated interaction partners within the Walker motifs of P-loop containing enzymes, suggests that this structural role of the Walker-A lysine is perhaps a widely deployed regulatory mechanism within this ancient family.